(untitled) (Law and world, 2015)
The article discusses today’s organizational and procedural problems of investigation. We have presented our concrete proposals for their resolution, in particular: we tried to show the role of criminology in opening and investigation of crime and its advantages in comparison with covert operative – investigative activities. We discussed the problems, on the basis of current Criminal Procedure Law, in connection with investigation and the investigator’s human rights situation, expressed opinions regarding the restoration of the investigation institute. We expressed our attitude toward the decision of government about restoration of justice. We expressed our opinions regarding the procedural agreement and the illegal judgments.